Concept mapping in STEM education: a meta-analysis of its impact on students’ achievement (2004–2023) - Xiao-Ming Wang; Jing-Lin Wang; Shu-Yan Xu; Si-Jie Xu (International Journal of STEM Education)
Abstract Concept mapping is a powerful educational tool that facilitates students' organization and integration of knowledge, leading to improved understanding and retention. Numerous studies have highlighted the potential of concept mapping to enhance students' achievement. However, comprehensive quantitative analyses focusing on its impact specifically in STEM education are limited. This meta-analysis synthesizes findings from 37 studies conducted between 2004 and 2023, identifying a moderate overall effect size of concept mapping on students' achievement in STEM disciplines (ES = 0.630). The analysis of six moderating variables (subject, educational level, duration of the experiment, concept map construction mode, learning equipment, and pedagogical approach) reveals that concept mapping is particularly effective in science and technology, with the greatest impact observed at the secondary education level. Interventions lasting between one week and one month yielded the most significant improvements in learning outcomes, especially when students independently constructed their concept maps. Both digital and paper-based tools demonstrated moderate and comparable effects on students' achievement. In addition, among various pedagogical approaches, contextual and inquiry-based pedagogical approaches are more effective when integrated into STEM education. This study provides recommendations for future research and practical implementation of concept mapping in educational contexts.